Chainsaw blue ; Simeon Banahaw ; For the people [videorecording] - Lazaro, Cheche; Banahaw, Simeon (Quezon City Probe Productions, 1989)
Tackles logging and its effects on environment ; a painter who draws inspiration from the mystical legends of Mt. Banahaw in Quezon City Province; and the massacre of "civilians" in Paombong, Bulacan when the military claims that those killed were NPA's or NPA symphatizers.
Chainsaw blue (18 min.) -- Simeon Banahaw (14 min.) -- For the people (19 min.)
VHS.
Keywords: Logging -- Philippines; Lumber trade -- Philippines; Art -- Philippines; Paintings -- Philippines; Insurgency -- Philippines; Counterinsurgency -- Philippines